THE INFLUENCE OF BUDGET PARTICIPATION ON REGIONAL GOVERNMENT PERFORMANCE WITH ORGANIZATIONAL COMMITMENT AND ORGANIZATIONAL CULTURE AS MODERATION VARIABLES: (Empirical Study on Regional Apparatus Organization (OPD) Bungo District Service) - Ronika Putri Ayu; Yudi Yudi; Muhammad Gowon (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2023)
This study aims to investigate the influence of budget participation on the performance of government areas, with organizational commitment as a moderating factor, and organizational culture as a moderator within the Regional Apparatus Organizations (OPD) Department in Bungo Regency. The population for this study consists of the Regional Apparatus Organizations (OPD) Department in Bungo Regency. The research sample was selected using the saturated sample method, which involves using the entire population as the research sample from 18 Regional Apparatus Organizations (OPD) Departments in Bungo Regency. The research employs a quantitative method, and primary data were collected through distributed questionnaires to respondents. This study found that involvement in budget decisions significantly impacts local government effectiveness. The influence of organizational culture on this relationship was also observed. However, there was no evidence of organizational commitment moderating this relationship. The coefficient of determination (R Square) indicates that regional government performance is influenced by budget participation, organizational commitment, organizational culture, and their interactions. These factors explain approximately 52.5% of the variation in government performance, with the remaining 47.5% attributed to unidentified factors outside the model.